Verify the identity .

(cscX-cotX)^2=1-cosX/1+cosX
_______

sorry i cant help you

(cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX
If you square this you have (1-cosX)^2/(sinX)^2
Now use (sinX)^2 = 1 - (cosX)^2 to get
(1-cosX)^2 / 1 - (cosX)^2 =
[(1-cosX)*(1-cosX)]/[(1 - cosX)*(1 + cosX)
Then simplify.

Similar Questions
  1. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
  2. express this in sinx(1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?? and B) express in cosx problem: is 1 +
    1. answers icon 1 answer
  3. express in sinx1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so
    1. answers icon 0 answers
  4. Prove the identitycscx+cotx-1/cotx-cscx+1 = 1+cosx/sinx
    1. answers icon 3 answers
more similar questions